The Sustainable Development Idea in the Management of European Metropolitan Areas - Danielewicz, Justyna (Economic and Environmental Studies, 2020)
The rapid urbanisation of the world leads, i.a., to dynamic development of metropolitan areas. The functional relationships between territorial units which make up a metropolitan area mean that in order to prevent negative effects of metropolisation and to ensure sustainable development of such an area, the preparation of economically, spatially and environmentally coherent strategies needs to be co-ordinated on the metropolitan level. This in turn requires that the approach towards managing development shifts in favour of governance. Using London and Copenhagen as case studies, this paper explores whether the concept of governance is used in managing metropolitan areas and weather metropolitan authorities integrate sustainable development principles in their policy documents. Research is based on the analyses of form of governance and strategic programmes adopted in metropolitan areas.